The Effect of High Irradiation Energy (Gamma, UV- light)Radiation on the Energy Gap of Polymers Doped with Anthrancene - Abdullah, Ahmed (Iraqi Journal of Science, 2025)
This research is related to the study of the energy gap of some glassy polymers (PC,PS and PMMA), we have studied the effect of gamma–ray and UV light radiation on the energy gap of these polymers and then the effect of dyes (anthracene) on the energy gap for these materials for exposure times (0 to 34 hr). It’s found that the energy gap of pure polymers and doped polymers measurement was changed depending on the gamma and UV dose and the mechanism of interaction between molecules of polymers and dye .It was found that the addition of anthracene to polymers leads to a reduction in the energy gap generally.